Design and experiment of a human-limb driven, frequency up-converted electromagnetic energy harvester. (December 2015) - Halim, Miah A.; Cho, Hyunok; Park, Jae Y.
Highlights: A frequency up-converted miniaturized energy harvester, driven by hand-shaking. Use of a freely movable ball conquers the inconvenience in resonance issue at frequencies below 10 Hz. Can be implemented to hand-held and wearable devices through efficient power conditioning circuitry. Abstract: We present a frequency up-converted electromagnetic energy harvester that generates significant power from human-limb motion (hand-shaking). Because the power generated by a vibration energy harvester is proportional to the operating frequency, the proposed energy harvester has been designed to up-convert the applied low-frequency vibration to a high-frequency vibration by mechanical impact. Upon excitation, a freely moveable ball (non-magnetic) within a cylindrical structure periodically hits two magnets suspended on two helical compression springs located at either ends of the cylinder, allowing these to vibrate with higher frequencies. The relative motion between the magnets and coils (wrapped around the outside of the cylinder) induces e.m.f. (voltage). High-frequency oscillators have been designed through the design parameters (i.e., frequency, spring stiffness, mechanical, and electrical damping), to minimize the power loss. A prototype was fabricated and tested both using a vibration exciter and by manual hand-shaking. The fabricated device showed non-resonant behavior during the vibration exciter test. At optimum load condition, the frequency up-converted generators (FUGs) delivered 0.84 mW and 0.96 mW of average power. A maximum 2.15 mW of average power was obtained from the device with series connected FUGs while it was mounted on a smart phone and was hand-shaken. The fabricated device exhibited 0.33 mW cm −3 of average power density, which is very high compared to the current state-of-the-art devices, indicating its ability in powering portable and wearable smart devices from extremely low frequency (∼5 Hz) vibration.